Comparing antioxidant capacity of purine alkaloids: A new, efficient trio for screening and discovering potential antioxidants in vitro and in vivo. (1st June 2015) - Tsoi, Bun; Yi, Ruo-Nan; Cao, Ling-Fang; Li, Shan-Bing; Tan, Rui-Rong; Chen, Min; Li, Xiao-Xiao; Wang, Chen; Li, Yi-Fang; Kurihara, Hiroshi; He, Rong-Rong
Graphical abstract: Highlights: An efficient trio was proposed for evaluation of antioxidant capacity. The trio considers both in vitro and in vivo antioxidant ability of food components. The trio is simple and economic compared with typical animal models. Caffeine and theacrine were found to possess potent in vivo antioxidant capacity. Abstract: The most commonly applied strategies for the evaluation of antioxidant capacity are the chemical- or cell-based approaches. However, the results obtained from these methods might not reflect the antioxidant ability of test samples within organisms. In this study, we propose a combination of experiments, including oxygen radical absorbance capacity (ORAC), cellular antioxidant activity assay (CAA), and the chick embryo model, as an efficient trio to evaluate antioxidant capacity of food components. Taking purine alkaloids as example, results demonstrate that chemical and cellular method might misinterpret their true ability on antioxidation. In chick embryo model, caffeine and theacrine can significantly improve vessel density on chorioallantoic membrane and myocardial apoptosis. The mechanism can be involving multiple targets within the organism. We believe that the trio proposed can be widely utilized in screening massive number of antioxidant in a cost-effective way. It will also help discovering new antioxidants that are easily being omitted due to their relatively poor in vitro activities.